Effect of plant growth regulators on vegetative growth and seed yield of coriander (Coriandrum sativum L.) cv. RCr – 435 - N L Sen, Piyush Verma (Journal of Spices and Aromatic Crops, 2006)
A field experiment consisting of nine levels of plant growth regulators (indole acetic acid,naphthalene acetic acid and gibberellic acid, each at 10, 25 and 50 ppm concentration) andthree modes of application (soaking of seeds, spraying 20 days after sowing and soaking +spraying) was conducted at Udaipur, Rajasthan, to study their effect on growth and yield ofcoriander (Coriandrum sativum). The results revealed that application of gibberellic acid 50ppm by soaking + spraying resulted in maximum number of nodes on main shoot (7.60),number of branches plant-1 (9.51), number of umbels plant-1 (25.36), biological yield (1.274 qha-1) and seed yield (0.432 q ha-1).